Study on Mist Nozzle Spray Characteristics for Cooling Application - Sapit, Azwan; Razali, Mohd. Azahari; Mohammed, Akmal Nizam; Manshoor, Bukhari; Khalid, Amir; Salleh, Hamidon; Hushim, Mohd Faisal (International Journal of Integrated Engineering, 2019)
Evaporative cooling mist spray is a cost effective solution for many cooling applications. Selection of misting spray nozzle play a major role in order to provide the suitable spraying condition in regards to the application. One of the most widely use mist spray application is evaporative cooling of outdoor open area. This study was carried out to characterized the spray formation, size of droplet, velocity of the droplet and the angle of the spray formation from a commercial mist spray nozzle namely 1/8 SF-CE SM nozzle with 1 mm and 2 mm diameter hole. Water was supplied with different pressure of 1, 2 and 4 bar. High speed video camera and still digital camera using short burst of flash were used to produce the video and image for analysis. The results show that increase in water pressure affect the spray angle, increase droplet speed and decrease droplet size of the mist spray.